Comparison of Central Venous Pressure (Cvp) Score among Patients on Mechanical Ventilator with Head of Bed (Hob) Elevation 30O; Neutral, Right, and Left Side Positions - Setiyawan Setiyawan; Kusman Ibrahim; Titin Mulyati (Jurnal Keperawatan Padjadjaran, 2019)
Early mobilization is important for critical patients to improve cough reflexes, eliminate bronchial secretions, facilitate work of mucociliary drainage muscles, and to prevent associated pneumonia ventilators and pressure sores. However, at the same time the patient often experiences vital signs change due to fluctuating conditions. Central Venous Pressure (CVP) measurement is oftenly needed to monitor central circulatory system. Unfortunately, in the clinical setting, the patient’s position must be changed first in a 30o neutral head of bed (HoB) position rather than left or right side HoB position. This study aims to examine the differences in of CVP score among patients on mechanical ventilation at HoB position elevation 30o in a neutral, right side, and left side position. This quantitative comparative study involved 24 subjects who were recruited consecutively. Data were analyzed using ANOVA. The results showed that the mean CVP value at neutral HoB position elevation was 13.5 ± 3.96, right sight HoB elevation was 12.8 ± 4.16, and left side HoB elevation was 14.4 ± 4.17. There was a significant difference (p <0.05) among those three positions. Post hoc analysis test found the HoB position 30o neutral vs left side possition was higher and signifficantly difference with HoB elevation 30o neutral vs right side positions (p<0.05). This study suggested nurses need to consider the change of CVP values while changing patiens’ position of HoB elevation 30o neutral, right side, and left side positions. Athough there was statistically difference among three positions, in fact, the value difference was less than 1 cmH2O which clinically did not see any differences.